PENGARUH PENERAPAN TEKNIK ONE TO ONE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 4 SUTERA KABUPATEN PESISIR SELATAN - Afrinaldi, Angli; Rahmi, Rahmi; Harisman, Yulyanti (STKIP PGRI Sumbar, 2013)
The research was motivated by the students comprehension of math concept is still low. This research aims to determine students comprehension of math concept by using one to one technique was better than students comprehension of math concept that was taught by using conventional learning, and to know the progress of studentsâ activity at eighth grade students of SMP 4 N Sutera, district of Pesisir Selatan that apply one to one technique.Type of this research was experimental research by using randomized control group only design.. The instrument used in this research is the ultimate test of students comprehension of math concept. Form of test used was essay with reliability test was r11 = 0,877 was bigger than rt = 0.404. It means the test result was reliable. Technique of data analysis used was T-Test one part the help of softwareMinitab.Based on the data analysis, it was found that both classes were distributed normally and homogeneous. The results of hypothesis test obtained P-Value= 0.040 it less than Î±=0.05, and based on the percentage of students activity was increased that was taught by one to one technique, with a variety of activities considered in this technique was the students were more active, in which the hypothesis of this research was accepted, so that it can be concluded that students comprehension of math concept by using one to one technique was better than students comprehension of math concept that apply conventional learning with confidence level was 95%.